Improving Seventh Grade Students’ Vocabulary Mastery Through Total Physical Response Method at SMP Negeri 3 Pangsid - Winda Aprilia; Syamsu T; Sitti Aisa; Nur Hikmah; Sam Hermansyah (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study examined whether the Total Physical Response (TPR) method significantly improved the vocabulary mastery of seventh-grade students at SMP Negeri 3 Pangsid. A quantitative approach with a one-group pre-test and post-test design was used. The population comprised 78 seventh-grade students in the 2025/2026 academic year, and 25 students from Class VII A were selected through purposive sampling. The research instruments were a 20-item multiple-choice vocabulary test and a classroom observation sheet. The test measured word meaning, pronunciation, and vocabulary use, while the observation focused on attention to commands, appropriate physical responses, active participation, and enthusiasm. The treatment was conducted in three instructional meetings through teacher commands, action modeling, repetition, individual and group responses, and simple role reversal. The results showed that the mean score increased from 66.60 on the pre-test to 85.60 on the post-test. The Shapiro-Wilk results indicated that both score distributions were normal, with significance values of 0.080 and 0.067. The paired sample t-test yielded a mean difference of 19.00 points, t(24) = -5.603, and p < 0.001. Classroom observation also showed that students paid attention, responded physically, participated actively, and demonstrated enthusiasm during TPR activities. These findings indicate that TPR significantly improved students’ vocabulary mastery and supported a more active, enjoyable, and low-anxiety learning environment.